Structural and functional studies of the promoter element for dengue virus RNA replication - Lodeiro, María F. (2008)
The 5' untranslated region (5'UTR) of the dengue virus (DENV) genome contains two defined elements essential for viral replication. At the 5' end, a large stem-loop (SLA) structure functions as the promoter for viral polymerase activity. Next to the SLA, there is a short stem-loop that contains a cyclization sequence known as the 5' upstream AUG region (5'UAR). Here, we analyzed the secondary structure of the SLA in solution and the structural requirements of this element for viral replication. Using infectious DENV clones, viral replicons, and in vitro polymerase assays, we defined two helical regions, a side stem-loop, a top loop, and a U bulge within SLA as crucial elements for viral replication. The determinants for SLA-polymerase recognition were found to be common in different DENV serotypes. In addition, structural elements within the SLA required for DENV RNA replication were also conserved among different mosquito- and tick-borne flavivirus genomes, suggesting possible common strategies for polymerase-promoter recognition in flaviviruses. Furthermore, a conserved oligo(U) track present downstream of the SLA was found to modulate RNA synthesis in transfected cells. In vitro polymerase assays indicated that a sequence of at least 10 residues following the SLA, upstream of the 5'UAR, was necessary for efficient RNA synthesis using the viral 3'UTR as template.